Criminological Study of Drug Distribution in Lubuklinggau City - Agustinus Samosir; Anak Agung Sagung Laksmi Dewi (Sociological Jurisprudence Journal, 2021)
Drug crimes are a serious crime against humanity, which has a tremendous impact, particularly on the young generation. Drug crimes also count as transnational crime, considering that the distribution and trade of drugs are executed illegally across national borders. As a legal state, to uphold the rule of law is to eradicate the distribution and use of narcotics, specifically in Lubuklinggau. This situation became the basis for us to explore the problem: how is the criminology study of drug distribution in Lubuklingau city?. The prevention of drug distribution in Lubuklinggau today needs improvement, particularly in terms of facilities. Advanced detection tool is necessary to improve the prevention of drug trafficking. Professional guidance and prevention efforts are made in various locations, such as government offices, schools, campuses, with supervision from police officers. The enforcement system also needs to give severe punishments to offenders.